Pelatihan Perakitan Komputer Pada SMK Tritech Indonesia - Hardianto, Hardianto; Wahyuni, Linda; Rosnelly, Rika; Nasution, M. Irfan Aldy; Harahap, Charles Bronson (Publikasi Pengabdian Masyarakat, 2024)
In the current era of globalization, computers are data processing machines and calculating tools, where the results or output can be printed via a printer. Input, process and output of a computer are the work processes of the 3 most important elements, namely hardware, software and users. Before users use a computer, in terms of assembling a computer, they need to know how to put together the parts needed to run the computer properly. Knowing the functions of the hardware components so that there are no mistakes in assembling a computer. Although assembling a computer is basically quite easy, some research is needed to get good results. There are many different price and quality options for computer assembly components. By assembling a computer yourself, we can choose the type of components, features, and computer facilities that best suit our needs. Before assembling a computer, you must prepare well, especially if there is hardware and software installed. Assembling and installing a computer is an important step in creating and maintaining a reliable and effective computer system. To ensure optimal system performance and security, a thorough understanding of assembly and installation methods is essential.